The epidemiology of pituitary adenomas in a community-based hospital: a retrospective single center study in Saudi Arabia - Aljabri, Khalid S.; Bokhari, Samia A.; Assiri, Faisal Y.; Alshareef, Muneera A.; Khan, Patan M. (Annals of Saudi medicine, 2016)
Data on pituitary adenoma (PA) prevalence in Saudi Arabia are scarce. To estimate the epidemiology of PA in a well-defined population. Retrospective analysis. Departments of Endocrinology and Radiology at King Fahad Armed Forces Hospital, Jeddah, Saudi Arabia. Radiological and hormonal data of patients with pituitary adenoma by MRI were reviewed for the period January 2008 to December 2015. Prevalence of PA and hormonal abnormalities. Of 537 patients; 249 subjects (46.4%), 70 (28.1%) males and 179 (71.9%) females, were diagnosed to have PA with mean age 36.3 (14.1) years. Microadenoma and macroadenoma were seen in 171 (69%) and 78 (31%) subjects, respectively. Microadenomas were more prevalent than macroadenomas (68.7% vs. 31.3%). Microadenomas were significantly more prevalent in females, 131 (73.2 %) vs. 40 (57.1%) whereas macroadenomas were significantly more prevalent in males, 30 (42.9%) vs. 48 (26.8%) (P < .001 for both comparisons). Patients with microadenomas were significantly younger than patients with macroadenomas (P < .0001). Advanced age was significantly associated with a larger PA size (r=0.39, P < .0002). Three types of hyperfunctioning PA were seen: prolactinoma, somatotroph adenoma, and corticotroph adenoma. Five types of hypofunctioning PA were seen: panhypopituitarism, secondary hypogonadism, growth hormone deficiency, central hypothroidism and central adrenal insufficiency. Non-functioning PA were within normal laboratory hormonal values in 2% of cases. Our study showed that the prevalence of PA was greater than previously reported. This increased prevalence may have important implications when prioritizing funding for research and treatment of PA. Clustering of cases within the study region might have affected estimates and limited study sample size.